A COMPARATIVE STUDY OF POLITENESS STRATGIES THROUGH IRONY AND INDIRECT SPEECH IN UZBEK AND ENGLISH DISCOURSE (SCIENCE TIME JOURNAL, 2026)
This study comparatively examines politeness strategies through irony and indirect speech in Uzbek and English discourse. The research analyzes how cultural values influence communicative behavior, particularly in requests, criticism, and interpersonal interaction. The findings reveal that English politeness mainly relies on syntactic hedging, modal verbs, and sarcasm to protect individual autonomy, whereas Uzbek politeness emphasizes hierarchy, collective harmony, honorifics, and indirectness through cultural respect. The study also highlights how differences in pragmatic norms may lead to intercultural misunderstanding. Ultimately, the research demonstrates that politeness is deeply shaped by linguistic and sociocultural frameworks.